IDENTIFIKASI PENGGUNAAN FORMALIN PADA TAHU PUTIH DI PASAR KEDUNGMUNDU DAN RANDUSARI SEMARANG - Bambang Sri Wahyono; Wikanastri Hersoelistyorini; Agus Suyanto (Universitas Muhammadiyah Semarang, 2016)
White tofu is a product of processed soybean food that has high water content and not durable. The practice of preservation is often done by the trader is to soak the tofu using formalin, so tofu is not easily destroyed, resistant to microorganisms, and can last up to seven days. Kedungmundu and Randusari markets are two major markets in Semarang, allegedly many food products sold contain harmful substances such as non-food preservative (formalin), dye clothes, and so forth. One food product that is suspected to contain harmful substances is white tofu. White tofu as one of the food products that many consumers demand, must be ascertained the quality. This study was conducted descriptively with qualitative examination of the presence or absence of formalin content in tofu analyzed by Chromatopic Acid and Resorcinol reagents. The organoleptic test used nonparametric statistical test with friedman test and continued wilcoxon test. The result of this study showed that most of the white tofu sold in Kedungmundu and Randusari markets positively contain formalin with a percentage of 71% in Kedungmundu market and 67% in Randusari market. Organoleptic assessment was in conformity with qualitative test results, samples with the highest average scores showed negative results and samples with the lowest average scores showed a formalin positive result.